Membrane Materials for Selective Ion Separations at the Water–Energy Nexus. Issue 38 (15th August 2021) - DuChanois, Ryan M.; Porter, Cassandra J.; Violet, Camille; Verduzco, Rafael; Elimelech, Menachem
Abstract: Synthetic polymer membranes are enabling components in key technologies at the water–energy nexus, including desalination and energy conversion, because of their high water/salt selectivity or ionic conductivity. However, many applications at the water–energy nexus require ion selectivity, or separation of specific ionic species from other similar species. Here, the ion selectivity of conventional polymeric membrane materials is assessed and recent progress in enhancing selective transport via tailored free volume elements and ion–membrane interactions is described. In view of the limitations of polymeric membranes, three material classes—porous crystalline materials, 2D materials, and discrete biomimetic channels—are highlighted as possible candidates for ion‐selective membranes owing to their molecular‐level control over physical and chemical properties. Lastly, research directions and critical challenges for developing bioinspired membranes with molecular recognition are provided. Abstract : Emerging water and energy technologies often require membranes that selectively separate an ion from similar species. Progress in enhancing selective ion transport in polymeric membranes is described, followed by analysis of three advanced material classes that are possible candidates for ion‐selective membranes owing to their molecular‐level control over physicochemical properties. Research directions and challenges for developing ion‐selective membranes are discussed.